Association Between Endometriosis and Prognosis of Ovarian Cancer: An Updated Meta-Analysis - Chen, Peng; Zhang, Chi-Yuan (Frontiers in Oncology, 2022)
Objective: Increased risk of ovarian cancer (OC) among endometriosis patients has been proposed. However, the association between endometriosis and prognosis of OC remains controversial. This study evaluated whether endometriosis had influence on the survival outcomes of OC through a meta-analysis. Methods: Relevant studies were retrieved from PubMed, Embase, and Web of Science databases and were evaluated using the Newcastle-Ottawa Quality Assessment Scale. Effect size was presented as hazard ratio (HR) and 95% confidence interval (CI). Heterogeneity test evaluation was performed using Cochran’s Q test and I2 statistics. Publication bias was determined using Egger’s test. Statistical analysis was performed using Stata 12.0 software. Results: Twenty-one studies involving 38641 patients were included. For the total OC, there were significant differences in overall survival (OS) [HR (95% CI)=0.67 (0.55, 0.80), P<0.001] and progression-free survival (PFS) [HR (95% CI)=0.58 (0.42, 0.81), P=0.001] between endometriosis-associated ovarian cancer (EAOC) and non-EAOC patients in the random-effects models (P<0.05). For ovarian clear cell cancer, there were significant differences in terms of OS [HR (95% CI)=0.63 (0.48, 0.83), P=0.001] and PFS [HR (95% CI)=0.67 (0.52, 0.87), P=0.002] between EAOC and non-EAOC patients in the fixed-effects models (P>0.05). Subgroup analysis suggested no significant differences between EAOC and non-EAOC in OS and PFS in the univariate analysis per subgroup, and PFS in the American subgroup (P>0.05). Conclusion: EAOC patients tended to have better OS and PFS than non-EAOC patients. Conducting higher quality prospective cohort studies with large sample sizes is recommended to confirm the authenticity of the current study’s results.